1976
DOI: 10.1017/s0022172400055704
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofShigella sonneiby fluid media

Abstract: Selenite F broth prepared in the laboratory from single ingredients was found to be significantly more efficient than nutrient broth in the isolation of Shigella sonnei from human faeces. It was more efficient than direct plating on deoxycholate citrate agar for diagnosisng Sonne dysentery in a local outbreak. The difference was significant. There was, however, no significant advantage for enrichment over direct plating when stools posted from Briston to Cardiff were examined. Laboratory prepared selenite F br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In addition extrinsic factors during incubation, particularly temperature, temperature fluctuations and a,, p02 and pC0z of the environment in which incubation takes place can dramatically influence the performance of a given medium. 1974;Harvey et al 1975;Fagerberg et al 1976;Nicholls et al 1976;Papadakis et al 1976;Price 1976;Staat 1976;Hanna et al 1977 should, therefore, be regular quality monitoring of all types of culture media (Mossel 1971;Vera 1971;Prier et al 1975;Stokes 1979). These include: (i) n u~t i o n a l dependence of the organisms in~ulated on or in the m e d i~; (ii) ~~g o n i s t i c ph~nomena, depending strongly on the so-called background association, present in the specimen (Mossel et al 1978~) and hence determined by the type and condition of the material under ~nv~stigation; and (iii) syner~sm between components of the microbial a~~i a t i o n of the specimen, as, for example, observed in sateIlite growth ( C h u r c~a n & Kahn 1921; Moon & Reinbold 1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition extrinsic factors during incubation, particularly temperature, temperature fluctuations and a,, p02 and pC0z of the environment in which incubation takes place can dramatically influence the performance of a given medium. 1974;Harvey et al 1975;Fagerberg et al 1976;Nicholls et al 1976;Papadakis et al 1976;Price 1976;Staat 1976;Hanna et al 1977 should, therefore, be regular quality monitoring of all types of culture media (Mossel 1971;Vera 1971;Prier et al 1975;Stokes 1979). These include: (i) n u~t i o n a l dependence of the organisms in~ulated on or in the m e d i~; (ii) ~~g o n i s t i c ph~nomena, depending strongly on the so-called background association, present in the specimen (Mossel et al 1978~) and hence determined by the type and condition of the material under ~nv~stigation; and (iii) syner~sm between components of the microbial a~~i a t i o n of the specimen, as, for example, observed in sateIlite growth ( C h u r c~a n & Kahn 1921; Moon & Reinbold 1976).…”
mentioning
confidence: 99%
“…Many more observations demonstrate deficiencies of selective media, which rely on delicate equilibria between productive and selective mechanisms of various sorts (Kligler 1918;Banwart & Ayres 1953;Burman 1955;Miller & Banwart 1965;Read & Reyes 1968;Taylor & Schelhart 1968;Wilson et al 1970;Reusze 1971;McCormack et al 1974;Moats & Kinner 1974;Mossel et at. 1974;Harvey et al 1975;Fagerberg et al 1976;Nicholls et al 1976;Papadakis et al 1976;Price 1976;Staat 1976;Hanna et al 1977 should, therefore, be regular quality monitoring of all types of culture media (Mossel 1971;Vera 1971;Prier et al 1975;Stokes 1979).…”
mentioning
confidence: 99%
“…We have not had the opportunity of testing strontium selenite broth (Iveson & Mackay-Scollay, 1969). Selenite F is also of value in the isolation of Shigella sonnei from stools (Price, 1976). From Table 2, however, it is possible that laboratory prepared Muller-Kauffmann tetrathionate might be useful in the examination of faecal samples arriving at the laboratory after postal delays.…”
Section: Resultsmentioning
confidence: 99%
“…to eliminate other intestinal bacteria. Price et al [7] reported, however, that S. sonnei could be isolated on agar plates after enrichment in selenite broth. We also sometimes found Shigella spp.…”
mentioning
confidence: 99%
“…An enrichment broth for Shigella spp. has been reported [7,8,[15][16][17] ; however, further development of more effective methods for the isolation of Shigella spp. is needed [11].…”
mentioning
confidence: 99%